Clarifying some complications in Khaghani’s poems in the framework of linguistic interference - Heydar Ebrahimi; Jamileh Akhyani; Moharram Eslami; Hossein Bakhshi (مطالعات زبانی و بلاغی)
Khāqāni’s poetry stands out in Persian poetry for its abundance of images, interpretations and concepts which makes his poems difficult to understand and  explain. Though, there have been valuable researches explaining the much more complicated aspects of the poems of this renowned Persian poet, there are still a great number of expressions and interpretations in his poems which have not been understood accurately. The hypothesis behind the present study is that part of the difficulty in understanding Khāqāni’s poetry is the phenomenon of linguistic interference. As one of the consequences of bilingualism, linguistic interferences refers to the (unconscious) influence of the speaker's mother tongue on her/his second language. It also includes the presence of regional beliefs and cultural characteristics in the speaker's speech and writing in second language. Based on the aforementioned hypothesis, the present study focuses on words, sentences, interpretations and idioms in Khāqāni’s poetry which could be understood only by considering their Turkish counterpart. Considering that Khāqāni is from Azerbaijan, and his poetry is written in Persian; there have been many historical discussions about the language of Azerbaijan in his time (12 AD). Away from such considerations, this study solely focuses on his own text to investigate the complications and problems in Khāqāni’s poetry, some of which are due to the poet's linguistic interference.